Analisis Kontribusi Literasi Keuangan dan Inklusi Keuangan Terhadap Kinerja Keuangan Sektor UMKM Di Kota Kupang - Antonius Yohanes William Timuneno; Maria Goreti Malut; Rifdah Riyan Dara; Grace Rianti Latuheru (Owner : Riset dan Jurnal Akuntansi, 2023)
This research was conducted at UKM Restaurant in Kupang City. The purpose of this study was to determine the effect of financial literacy and financial inclusion on the financial performance of UMKM Restaurants. This research uses a quantitative approach or it is also called a positivistic method because it is based on a positivism philosophy. To determine the sample using Simple Random Sampling and the sample used in thi sstudy were 50 respondents to the Restaurant in Kupang City as the primary data source, and data collection used a questionnaire (questionnaire) distributed at the Restaurant Kupang City. The data analysis technique used in this study is multiple linear regression analysis, t test and f test. The results of this study indicate that the variables of financial literacy and financial inclusion partially or simultaneously have a positive and significant effect on the financial performance of UMKM at Restaurants in Kupang City. Suggestions from this research are for restaurants to explore more about finance, for cooperatives & UMKM offices and financial institutions so that they can provide more education for the community and for further researchers it is hoped that they can add indicators and other variables.